Supersensitivity of the Cholinergic Muscarinic System in the Rat”™s Brain is Induced by High Concentrations of Cu+2 - Gutiérrez Reyes, Elsa; Castañeda Perozo, Darwin; Papale Centofanti, Jhan; Nello Pérez, Carlota; Pascuzzo Lima, Carmine; Moreno Yanez, José; Bonfante Cabarcas, Rafael (Investigación Clínica, 2009)
Transition metals have been described as regulators of receptor”™s function. Here, we studied the effects of chronic administration of Cu2+ or the Cu2+ chelator penicillamine (PA) on the functional and binding properties of the muscarinic receptors (MR) on selected areas of rat”™s brain. Groups of 10 Sprague-Dawley rats were treated daily, for 45 days with either 1)Â 1mg/Kg CuSO4 (Cu2+), 2) 100 mg/Kg PA, or 3) saline solution. Double T-maze and motility cages were used for behavioral testing and the binding assays were performed using [3H]-QNB or [3H]-N-MSCP as MR”™s ligands. Cu2+ brain levels were measured in the cerebral cortex by atomic absorption spectrophotometer. Results showed that PA treated rats displayed a significant decrease of locomotor”™s activity (LA) and rearing behavior (RB), but a significant increases in memory efficiency (ME). Cu2+ treated rats displayed diminished RB with no significant changes in LA. Cu2+ treated rats displayed higher MR”™s density (Bmax) in cortex (C), striatum (S), and hippocampus (H). An increase in Bmax was also observed in PA treated rats, but only in C and S. Finally, Cu2+ tissue concentration was significantly higher in C of both Cu2+ and with PA treated animals. In conclusion, 45 days of Cu2+ or PA treatment induced brain hypercuprosis, which was associated with MR binding supersensitivity; however, change in ME was only observed in PA treated rats suggesting that might be still another factor in these experiments besides Cu2+ (i.e., Zn2+ or PA itself) involved in memory modulation